p-hydroxy benzaldehyde attenuates intestinal epithelial barrier dysfunction caused by colitis via activating the HNF-1β/SLC26A3 pathway - Liu, Meng; Wang, Yuhui; Xu, Xiaotian; Guan, Guoqiang; Zhang, Shu; Zhu, Shengnan; Liu, Yang; Zhu, Yizhun; Duan, Xiaoqun (Frontiers in Pharmacology, 2024)
Background Intestinal epithelial barrier dysfunction is intricately linked to the pathogenesis of ulcerative colitis (UC). Dietary interventions that bolster intestinal epithelial barrier function can effectively thwart UC onset. Our prior research revealed that p-Hydroxy benzaldehyde (HD), a phenolic compound from Nostoc commune (an edible cyanobacterium), markedly upregulated the expression of E-cadherin, a pivotal protein in intestinal mucosa, thereby mitigating mucosal damage in mice afflicted with dextran sulfate sodium (DSS)-induced colitis. Nevertheless, the precise molecular mechanisms underpinning HD’s ameliorative effects on intestinal epithelial barrier dysfunction remain elusive. Methods Dextran sodium sulfate (DSS)-induced colitis mouse model was established, and the successful establishment of the model was determined by evaluating the changes in body weight, disease activity index (DAI), colonic histopathology, and white blood cell count. Transmission electron microscopy (TEM) observed the ultrastructural changes of intestinal villi. The levels of inflammatory factors ( IFN-γ IL-13 ) and intestinal permeability indicators (FITC-Dextran, DAO, ET, and D-LA ) were detected by Enzyme-linked immunosorbent assay (ELISA). Western blotting (WB) and immunohistochemistry (IHC) were used to detect the expression of intestinal barrier integrity-related factors such as tight junction protein TJs (ZO-1, occludin) and adhesion junction protein AJs (E-cadherin). Furthermore, WB, Pull-down assay, drug affinity reaction target stability (DARTS) assay, molecular docking and molecular dynamics (MD) simulation were used to determine the potential target and molecular mechanism of HD. Results HD intervention significantly alleviated the symptoms of colitis mice, inhibited the weight loss and colon shortening, reduced DAI score and colon pathological score, maintained the ultrastructure of intestinal villi in colon tissue, and significantly reduced the inflammatory factors IFN-γ, IL-13 and the number of white blood cells in colon tissue of colitis mice. HD could also reduce the levels of FITC-Dextran, DAO, ET, and D-LA and increase the expression of ZO-1, occludin, and E-cadherin in the colonic tissues of colitis mice, thereby maintaining the impaired intestinal barrier function caused by colitis. Mechanically, HD augmented the expression of hepatocyte nuclear factor 1β (HNF-1β) and DRA. Adeno-associated virus (AAV)-HNF-1β shRNA or Lentivirus-mediated HNF-1β knockdown effectively abolished HD-induced intestinal barrier protection, as well as the promotion of solute carrier family 26 member 3 (SLC26A3) expression levels. SLC26A3 siRNA effectively reversed the inhibition of intestinal permeability by HD. Pull-down assay, DARTS analysis, molecular docking, and MD results showed high binding strength, interaction efficiency and remarkable stability between HNF-1β and HD. Conclusion This study elucidates HD’s role in forestalling intestinal epithelial barrier disruption under colitis conditions. Mechanistic investigations revealed that HD fortifies TJs and AJs expression via the HNF-1β/SLC26A3 pathway, thus preserving the lower intestinal epithelial barrier’s integrity in UC.